OPTIMALISASI WAKTU PENGIRIMAN DAN EFISIENSI BIAYA OPERASIONAL UNTUK MENINGKATKAN EFEKTIVITAS KINERJA DIVISI TRUCKING PADA PT PERISHABLE LOGISTICS INDONESIA - Hidayat, Cecep Edi; Suhartono, Suhartono; Kamela, Hurian; Pujia, Dede Puspa (Bisnis-Net, 2026)
This study aims to analyze efforts to optimize delivery time and operational cost efficiency in order to improve the performance effectiveness of the Trucking Division at PT Perishable Logistics Indonesia. The background of this research arises from operational challenges faced by the company, such as unpredictable travel times, delays during the cargo pick-up process, and high operational costs that affect productivity and service quality. The research method employed is a quantitative approach with multiple regression analysis, in which data were collected through questionnaires distributed to employees of the Trucking Division. The results indicate that optimizing delivery time has a significant influence on improving performance effectiveness, while operational cost efficiency also contributes positively to achieving service targets and reducing resource waste. In conclusion, the synergy between improving delivery time management and controlling operational costs can serve as a key strategy to enhance the performance of the Trucking Division, while also strengthening the company’s competitiveness in the logistics industry.